Isolamento e cultivo de microalgas em resíduo líquido do processamento da mandioca: manipueira - Cartas, Liliana Carrillo (Universidade Federal do Tocantins, 2018)
The objective of this research was to evaluate the viability of the cassava waste water as a culture medium for microalgae and to determine the best conditions for cultivation. The strains evaluated were isolated from the stabilization lagoons of the company Podium Foods LTDA. of Paranavaí, being morphologically identified as Chlorella sp., Scenedesmus sp. Monoraphidium sp. and Golenkinia sp. The presence of amylolytic activity and determination of cyanide toxicity, a compound present in the residue, were evaluated for each of the isolated microalgae strains. The presence of amylase was identified in Monoraphidium sp, Golenkinia sp. and Scenedesmus sp. when inoculated in 0.2% agar-starch solid medium. The cyanide tolerance was evaluated by simulating the cyanogen environment with addition of KCN in the autotrophic culture medium. The microalgae Monoraphidium sp. and Scenedesmus sp. demonstrated the capacity to develop in medium containing up to 200ppm of KCN, while the microalgae Chlorella sp. and Golenkinia sp. have sustained maximum concentrations of 40 ppm. In order to evaluate the survival of microalgae when cultivated in the liquid cassava processing residue, non-sterile cassava waste water handling, sterile manipulative cassava waste water and pre-treated cassava waste water (anaerobic digestion) were used in different concentrations. The tests were carried out in 125 mL Erlenmeyer flasks, under 2500 Lux illumination, 12-hour light/dark photoperiod and 25 °C temperature. Initial inoculum concentrations were 0.2 g.L-1. In the experiments conducted with the non-sterilized raw cassava waste water, all microalgae showed development at concentrations of 10% v/v of the residue (cassava waste water/water). The microalga Monoraphidium sp. which reached a maximum productivity of 0.014 day-1, only 5% lower than that achieved when cultivated in an autotrophic medium. Already in the crops in sterile cassava waste water, the four microalgae strains tested showed a higher resistance to the medium of up to 30% of the residues. The highest productivity was observed with the microalga Monoraphidium sp. and Golenkinia sp. which was 0.078 day-1 and 0.018 day-1 respectively at the 10% v/v concentration of cassava waste water. In the experiments carried out in cassava waste water after anaerobic digestion, concentrations up to 100% of the residue were supported for the isolate of Monoraphidium sp., Golenkinia sp., and Scenedesmus sp., and up to 40% v/v for the microalga Chlorella sp. The highest specific growth rate was with the microalga Monoraphidium sp. in the concentration of 40% of cassava waste water (v/v) being 0.12 day-1. The microalgae Golenkinia sp. and Scenedesmus sp. also showed efficiency when cultivated in the digested effluent, and at concentrations of 20% v/v cassava waste water/water, presented growth similar to that obtained in the synthetic medium. The results showed that it is possible to cultivate microalgae in cassava waste water raw, treated and even digested cassava waste water. However, suitable treatments must be identified for increased microalgae productivity. The microalgae Monoraphidium sp. and Scenedesmus sp. demonstrated to be able to survive and grow better in anaerobically digested effluent cultivation, thus, the use of the digested cassava waste water as a culture medium is shown as an efficient way of producing large amounts of microalgae biomass.